2005
DOI: 10.4269/ajtmh.2005.73.977
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Sarcoptes Scabiei and Dermatophagoides Pteronyssinus Glutathione S-Transferases: Implication as a Potential Major Allergen in Crusted Scabies

Abstract: The astigmatid mite Sarcoptes scabiei is the causative agent of scabies, a highly infectious parasitic disease of the skin. Although the mite causes marked hypersensitivity reactions, particularly in crusted (severe) scabies, little is known about the specific scabies mite molecules involved in such immunologic responses. We have identified six genes encoding scabies mite homologues of mu and delta-like glutathione S-transferases (GSTs) as well as novel house dust mite GSTs. A mu class S. scabiei GST was subcl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 47 publications
2
42
0
Order By: Relevance
“…The cloning of SM proteins corresponding to those of the predominant HDM allergens has now facilitated studies of their sequence homology (25,26,34,45,46,49,50), localization (47,51), enzymatic activity (7,16,22,35,40), and interactions with the immune system (8,11,30). Here, we have studied differences in the types and magnitudes of the systemic antibody and cellular responses to characterize the specific immune response in OS and compare it to the more severe and debilitating crusted form of the disease (CS).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cloning of SM proteins corresponding to those of the predominant HDM allergens has now facilitated studies of their sequence homology (25,26,34,45,46,49,50), localization (47,51), enzymatic activity (7,16,22,35,40), and interactions with the immune system (8,11,30). Here, we have studied differences in the types and magnitudes of the systemic antibody and cellular responses to characterize the specific immune response in OS and compare it to the more severe and debilitating crusted form of the disease (CS).…”
Section: Discussionmentioning
confidence: 99%
“…Purified proteins (0.5 to 1 g/lane), including S. scabiei GST as a control protein (16), were resolved on 12% SDS-PAGE reducing gels for 60 min at 125 V DC, with Benchmark prestained protein ladders (Invitrogen Pty Ltd., Victoria, Australia) as molecular mass standards. Gels were stained with Coomassie blue R250 (Sigma-Aldrich, Sydney, NSW, Australia) or, for Western blotting, transferred to nitrocellulose membranes (Schleicher and Schuell, Dassel, Germany) for 60 min using standard methods (9,44).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…vulpes (43,44,70), and large expressed sequence tag databases containing both partial and complete DNA sequences of S. scabiei genes have been established. From these databases, scabies mite homologues to most of the known house dust mite allergens have now been identified, as well as many other relevant molecules (33,43,61,62,75,91). Recombinant antigens promise a continuous, reproducible quantity of allergenic proteins in a purified form suitable for use in in vitro assays.…”
Section: S Scabiei Gene Discoverymentioning
confidence: 99%
“…These include mature forms of both active and inactive homologues of the cysteine protease group 1 allergens (62), mature forms of active and inactive homologues of the serine protease group 3 allergens (61), a mu class and a delta class glutathione S-transferase group 8 allergen (33,91), and a homologue to the C terminus of an apolipoprotein group 14 allergen (51). Immunohistochemical staining of sections of human skin which was highly infested with S. scabiei mites showed that anti-group 8 and anti-group 14 antibodies (generated in mice and rabbits, respectively) localized to the internal organs of the scabies mites and the cuticle, with minor staining in the digestive system (51) (Fig.…”
Section: S Scabiei Allergensmentioning
confidence: 99%